PENGUATAN STATUS KELEMBAGAAN LEMBAGA PENYIARAN PUBLIK (STRENGTHENING STATUS OF INSTITUTIONAL PUBLIC BROADCASTING INSTITUTE) - Denico Doly (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2012)
Public Broadcasting (LPP) in Indonesia under the Broadcasting Act, which then further stripulated in Government Regulation. The presence of LPP is very important, this is because the LPP duty to provide information, education, and entertainement to the public in accordance whit what is needed by the community. The presence of LPP at this time is decreasing, this is because people prefer to see broadcast by privete broadcasting intitutions or subscribed broadcasting. This problem is due to LPP as broadcaster can not provide an attractive packaging in broadcasting activities. The main problem of the LPP is still unclear institutional sctructure and the organization of LPP. Strengthening LPP recognized as a state institution in Indonesia should be immediately carried out, this is due to the need for broadcasting activities oriented to the needs of community.ABSTRAKLembaga Penyiaran Publik (LPP) di Indonesia diatur dalam UU Penyiaran, yang kemudian diatur lebih lanjut dalam Peraturan Pemerintah. Keberadaan LPP sangat penting, hal ini dikarenakan LPP bertugas untuk memberikan informasi, pendidikan dan hiburan kepada masyarakat sesuai dengan apa yang dibutuhkan oleh masyarakat. Keberadaan LPP pada saat ini menjadi lemah, hal ini dikarenakan masyarakat lebih memilih melihat siaran yang dilakukan oleh Lembaga Penyiaran Swasta atau Lembaga Penyiaran Berlangganan. Permasalahan ini dikarenakan LPP sebagai lembaga penyiaran tidak dapat memberikan kemasan yang menarik dalam kegiatan siarannya. Permasalahan utama dari LPP yaitu masih tidak jelasnya struktur kelembagaan dan juga organisasi dari LPP tersebut. Penguatan LPP sebagai lembaga negara yang diakui di Indonesia harus segera dilakukan, hal ini dikarenakan perlu adanya kegiatan penyiaran yang berorientasi kepada kebutuhan masyarakat.